Studi Kategorisasi Pengunjung Kawasan Bersejarah Berdasarkan Preferensi, Persepsi, Keinginan Berkunjung Kembali, Kegiatan dan Mitra - Wulansani, Nyoman Laksmitasari; Kusuma, Hanson E; Riska, Annisa Safira (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2021)
The heritage area is one of many tourism destinations in the world. Indonesia has many heritage areas that had been known as world cultural heritage sites. The development of heritage areas could be done by the exploration of visitor needs. The main goal of this research is to know about visitor needs and grouping in the heritage areas. The data was collected by distributing questionnaires online. The data analysis method used in this study consisted of three steps, open coding, axial coding, and selective coding. From the results of the correspondence analysis between preferences, perceptions, desire to revisit, activities, and partner there are three groups were found, namely will revisit, hesitate to revisit, and will not revisit. The â€œwill revisitâ€ group who not only care about cultural heritage but also other attributes, have various activities, and visit groups or individuals. The â€œhesitateâ€ group prioritize visual quality and facilities, engage in educational, sporting, or recreational activities, and are more likely to visit with friends. Last one, the â€œwill not revisitâ€ group who felt that they did not fit the atmosphere in the historical area, work in this area, and come with a partner.